2018
DOI: 10.1108/ijoem-03-2017-0081
|View full text |Cite
|
Sign up to set email alerts
|

Does Islamic equity investment provide diversification benefits to conventional investors? Evidence from the multivariate GARCH analysis

Abstract: Purpose The purpose of this paper is to quantify the extent to which the Malaysia-based equity investors can benefit from diversifying their portfolio into the conventional and Islamic Southeast Asian region and the world’s top ten largest equity indices (China, Japan, Hong Kong, India, the UK, the USA, Canada, France, Germany and Switzerland). Design/methodology/approach The multivariate GARCH-dynamic conditional correlation is deployed to estimate the time-varying linkages of the selected conventional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 72 publications
1
28
0
Order By: Relevance
“…The kurtosis values represent the fatness of the tails of the distribution and distribution of data around the mean. All the kurtosis values are greater than 3 which show that data are not normally distributed [59,60]. The Jarque-Bera test of normality rejects the null hypothesis of normality at 1% significance level.…”
Section: Descriptive Statisticsmentioning
confidence: 83%
See 3 more Smart Citations
“…The kurtosis values represent the fatness of the tails of the distribution and distribution of data around the mean. All the kurtosis values are greater than 3 which show that data are not normally distributed [59,60]. The Jarque-Bera test of normality rejects the null hypothesis of normality at 1% significance level.…”
Section: Descriptive Statisticsmentioning
confidence: 83%
“…The diagonal elements of the covariance matrix represent the unconditional volatilities. We found that value of unconditional volatility in all the markets is near to 1 which is considered to be the high volatility in returns [56,60]. Table 8 reports the values for unconditional volatility ranking in which China shows the highest unconditional volatility, while Malaysia shows the lowest unconditional volatility, which indicates the stability in the Malaysian stock market.…”
Section: The Unconditional Volatility and Correlationsmentioning
confidence: 87%
See 2 more Smart Citations
“…Charles et al (2015) have argued that because Islamic indexes are subjected to less diversification as they predominantly focus on particular sectors, they have a significantly higher risk. Likewise, Saiti et al (2014) and Saiti and Noordin (2018) found that Islamic stock indexes do not provide the extra benefit of diversification in comparison to their conventional counterparts. In a similar vein, Albaity and Ahmad (2008) claimed that conventional equity indexes are less risky in comparison to their Islamic counterparts given fewer diversifications.…”
Section: Introductionmentioning
confidence: 99%